What motivates exchangeable debt offerings? - Danielova, Anna N.; Smart, Scott B.; Boquist, John (Journal of Corporate Finance, 2010)
Debt that is convertible into shares of a company other than the issuer is called exchangeable debt. Most firms that issue exchangeable debt hold large blocks of shares in several companies, and in this paper we study factors that influence the selection of a particular block to serve as the underlying asset for an exchangeable debt issue. Comparisons between issuers' holdings in different firms shed light on issuers' performance as monitors as well as their ability to engage in market timing. Holdings attached to these issues display superior past operating performance, but after the offer, both operating performance and stock returns decline. In contrast, we do not find similar systematic performance patters for the “other holdings” of exchangeable debt issuers.